Inferior vena cava parameters predict re‐admission in ischaemic heart failure. (8th February 2014) - Carbone, Federico; Bovio, Marta; Rosa, Gian Marco; Ferrando, Fabio; Scarrone, Alberto; Murialdo, Giovanni; Quercioli, Alessandra; Vuilleumier, Nicolas; Mach, François; Viazzi, Francesca; Montecucco, Fabrizio
Abstract Background The clinical history of heart failure (HF) is usually characterized by frequent hospitalizations for decompensation. Therefore, several markers of subclinical hemodynamic congestion are under investigation for predicting early rehospitalization. In this field, the potential of ultrasound inferior vena cava (IVC) assessment has been recently investigated in HF but not yet assessed in the different aetiological categories. Material and methods Forty‐eight patients admitted for decompensated HF (n = 25 with ischaemic heart disease [IHD] and n = 23 non‐IHD) underwent biochemical examination (including NT‐proBNP), echocardiography and IVC assessment by hand‐carried ultrasound (HCU). During 60‐day follow‐up after discharge, the re‐hospitalization rate for HF was recorded to investigate the predictive power of NT‐proBNP and IVC assessment among the two study groups. Results IHD and non‐IHD patients with HF were similar except for gender distribution. During follow‐up, 16·7% of patients were rehospitalized for decompensated HF, with higher prevalence in IHD group (28% vs. 4·3% P = 0·031). IVC assessment at discharge significantly predicted re‐admission in the overall population and in IHD group, whereas NT‐proBNP failed to predict rehospitalization in IHD group. In adjusted hazard ratio, only IVC min and the changes of IVC from admission significantly predicted re‐admission. ROC analysis confirmed the change in IVC min as the best predictor of rehospitalization in patients with IHD. Conclusion This pilot study showed a higher early re‐admission rate in patients with HF due to IHD. In addition, the change in IVC min diameter from admission to discharge was the best predictor of re‐admission in patients with IHD.